Effect of starch and inorganic nitrogen on microbial transformations of organic compounds in soil - Novák, B (Folia microbiologica, 1980)
It was found in long-term incubation experiments (100 weeks) that in soil non amended with organic compounds, mineralization proceeded in a steady state after an initial reactive respiration and corresponded approximately to the rate of mineralization of soil organic matter under natural conditions. The addition of nitrogen influenced this mineralization process only very slightly. The addition of starch decreased the stability of organic compounds in the soil at first but the newly formed organic substances were gradually stabilized again. The addition of nitrogen to starch increased the extent and the rate of these alterations. The overall extent of mineralization of the substrate after the addition of starch alone exceeds the amount of the added substrate; a small accumulation of the substrate could be observed after the addition of starch together with nitrogen.
Keywords: biotransformace; Carbon; dusík; průmyslová hnojiva; Biotransformation; Stimulation, Chemical; Soil Microbiology; škrob; chemická deprese; Starch; půdní mikrobiologie; chemická stimulace; Fertilizers; Depression, Chemical; uhlík; Nitrogen